Diseño del sistema de filtración de aguas para consumo en la comunidad Las Balsas (Parroquia San Gregorio - Cantón Muisne) - Arboleda Tulcanaza, René Sebastián (2015)
Ecuador is a country where the use of alternative sources of non-conventional water occurs frequently, especially in areas or villages far away from sources of safe water. The present study is meant to develop and measure the effectiveness of removing contaminants from a water filter for Las Balsas community, located in the parish of San Gregorio, Muisne; under controlled conditions in order to obtain data on pollutant removal and then identification of the best alternatives for appropriate treatment to comply with the maximum permissible values established by the national laws. The data collection was performed on two occasions where samples of both raw water was taken untreated, such as water and treated water by the implanted in the community system further the community system with 3 types of similar systems but compared two variants: the first variant was the height of the filter bed and the second was the retention time of the water in the system. The results obtained are placed within the maximum permissible limits of the reference standard INEN 1108, making the systems used are adequate for proper treatment, however there was a case in which it was not possible to comply, in the case of the microbiological parameter fecal coliform so it is necessary to supplement the treatment with chlorination to completely eliminate this parameter..